P775Molecular, label-free imaging for characterization of cardiomyopathy in mice. (15th July 2014) - Poitz, D M; Steinbronn, N; Barthel, P; Koch, E; Steiner, G; Strasser, RH
Abstract: Mice lacking Caveolin-1 (cav1ko) develop a severe hypertrophic cardiomyopathy (HCM). The HCM in this model is induced by an uncoupling of the endothelial NO-synthase, which leads to the enhanced production of radicals. The main characteristic of this form of cardiomyopathy is a thickened ventricle due to remodelling processes of the extracellular matrix composition mainly mediated by collagen deposition. However, the imaging of cardiomypathic tissue is still restricted to conventional histochemical analysis. Therefore, the aim of the present study was to characterize the myocardial tissue of cardiomyopathic cav1ko mice compared to wildtype C57BL6 mice (wt) by using Fourier Transformed Infrared (FT-IR) micro spectroscopic imaging. 15 weeks old wt or cav1ko mice were used to prepare thin cryosections of the hearts. Serial sections were prepared for spectroscopical analysis, hematoxylin-eosin staining and classical immunostaining of Collagene 1, 3 and 4. FT-IR micro spectroscopy was performed using the Bruker Hyperion system. Spectra were collected in transmission mode using a resolution of 6 cm-1 in a spectral range of 950–3800 cm-1. Approximately 25.000 individual spectra of each sample were acquired. IR spectra of cardiac samples show two strong bands namely the amide I (1650 cm-1) and amide II (1550 cm-1) modes. In addition, significant bands were observed around 1400 cm-1 (vibrations of fatty acids) and at 1460 cm-1 (CH2 bending vibrations). Absorption bands of nucleic acids were found between 1000 cm-1 and 1200 cm-1. Initially, the data set was evaluated by k-means clusters analysis. This analysis reveals that wt and cav1ko hearts significantly differ in their biochemical composition. To obtain detailed molecular information, a principal component analysis (PCA) was applied to the data. PCA shows, that cav-1 ko mice had a higher content of collagen within the ventricle. By comparison with the classical immunohistochemical stainings of the different collagen types in concert with the loading plots of the different principal components, the results of PCA allowed an identification of different collagen types and an objective quantification of the collagen content. In addition, the analysis of the bands representing nucleic acids revealed a lowered DNA content in cav-1 ko mice per area which is due to the hypertrophy of the ventricle. In conclusion, these results enlighten the capability of FT-IR micro spectroscopy for the label free and objective identification of cardiomyopathic heart failure by characterising the structural changes within the myocardial tissue.